2017
DOI: 10.1093/cid/cix210
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ebola RNA Persistence in Semen: A Report From the Postebogui Cohort in Guinea

Abstract: This study modeled the presence of Ebola virus RNA in the semen of male Ebola survivors participating in the Postebogui study in Guinea. The median time of reverse-transcription polymerase chain reaction negativity was 46.4 days after symptom onset (95% confidence interval, 11-82.6). The results emphasize the importance of the World Health Organization recommendations for survivors' management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
1
21
0
1
Order By: Relevance
“…There have been nine seminal/testicular persistence longitudinal cohort studies since 1995 that have followed a total of 158 persistent male survivors with seven studies conducted during the West African EVD epidemic [22,23,24,26,29,62,131,133]. Two studies examining the 1995 EVD outbreak in Kikwit, Democratic Republic of the Congo, identified eight males with persistent EBOV in their semen [26].…”
Section: Male Testicular Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…There have been nine seminal/testicular persistence longitudinal cohort studies since 1995 that have followed a total of 158 persistent male survivors with seven studies conducted during the West African EVD epidemic [22,23,24,26,29,62,131,133]. Two studies examining the 1995 EVD outbreak in Kikwit, Democratic Republic of the Congo, identified eight males with persistent EBOV in their semen [26].…”
Section: Male Testicular Persistencementioning
confidence: 99%
“…In comparison, the recent West African EVD epidemic lasted two years and resulted in 28,652 cases and 11,325 fatalities across three countries (including suspect, probable, and confirmed cases) [19]. After the West African epidemic subsided, surveillance of EVD survivors revealed that EBOV persists in the male reproductive tract for extended periods of time in the absence of symptoms [21,22,23,24]. While persistence had been noted in cases studies in previous outbreaks of EVD and MVD, the scale of the West African epidemic led to targeted surveillance of survivors in numbers suitable for statistical analysis [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The program aimed to mitigate the risk for EVD reintroduction from exposure to survivors' body fluids. We were able to enroll ≈90% of the survivors in Guinea and test the semen of >90% of the enrolled male survivors >15 years of age, an unprecedented rate compared with other survivor monitoring programs (19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Across multiple studies, it has been shown that the cross-sectional percentage of EBOV survivors of the 2014–2015 West African epidemic with a positive RT-PCR for EBOV RNA in the semen ranges from 8.1 to 9.8%. 41 , 42 , 43 , 44 , 45 With more living EBOV survivors from this epidemic than ever before, this number represents a considerable pool of individuals. While disease modeling has shown that 50% of individuals will clear the virus from semen at 115 days and 90% will clear it at 294 days, viral EBOV RNA has been detected in the semen for as long as 965 days after initial infection.…”
Section: Methodsmentioning
confidence: 99%